2008
DOI: 10.1002/ca.20665
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue anatomy around the hip and its implications for choice of entry point in antegrade femoral nailing

Abstract: Antegrade intramedullary nailing is an accepted method of treatment for femoral shaft fractures. Entrance of the nail through the trochanteric fossa is currently recommended by some surgeons. This approach results in some cases, however, in loss of abduction strength and persistent pain. Nail insertion at the tip of the greater trochanter may be more favorable. In this study the anatomical relationships of the trochanteric fossa and of the tip of the greater trochanter were explored. Dissection was carried out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The terminology in the literature regarding this attachment site is variable, being described as: “digital fossa” (Gray et al, ), “pit” (Lumley et al, ) and “depression” (Tortora and Derrickson, ) on the posterior aspect of the medial surface of the greater trochanter (Papadakis et al, ; Ito et al, ). In many reports, OE is described as inserting into the “piriform fossa” (Moein et al, ; Solomon et al, ) while, in a study of eight cadavers, Robinson et al () identified the OE insertion as the “trochanteric fossa”. Although, the discrepancy in the terminology has been discussed by Papadakis et al () in an attempt to improve the accuracy and reliability of the intramedullary nailing surgical procedure, it persists.…”
Section: Resultsmentioning
confidence: 99%
“…The terminology in the literature regarding this attachment site is variable, being described as: “digital fossa” (Gray et al, ), “pit” (Lumley et al, ) and “depression” (Tortora and Derrickson, ) on the posterior aspect of the medial surface of the greater trochanter (Papadakis et al, ; Ito et al, ). In many reports, OE is described as inserting into the “piriform fossa” (Moein et al, ; Solomon et al, ) while, in a study of eight cadavers, Robinson et al () identified the OE insertion as the “trochanteric fossa”. Although, the discrepancy in the terminology has been discussed by Papadakis et al () in an attempt to improve the accuracy and reliability of the intramedullary nailing surgical procedure, it persists.…”
Section: Resultsmentioning
confidence: 99%
“…Stannard et al [3] reported intraoperative parameters including fluoroscopy time and duration of surgery to be better in the GTE group with no differences in functional outcomes. Although some cadaveric studies have claimed that the GT entrance may decrease morbidity due to a reduction in soft tissue injury, [5] other clinical studies have shown that functional outcomes, particularly in regard to the gluteus medius, abductor muscles, and tensor fasciae to be similar between different entrance points [3]. However, only a handful of studies have directly compared the effects of the entrance point among supra-isthmal, isthmal, and infra-isthmal femoral shaft fractures [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, the duration of postoperative stay in the hospital was longer in the TFE group, likely due to the higher number of open reductions performed in this group. Although several authors have recommended the use of a more lateralized entrance for treatment of femoral shaft fractures, [1,5,12], further studies have revealed that despite developments in the design of GTE nails, more iatrogenic fractures with associated varus malalignment can be anticipated [13]. However, previous studies had not classified these fractures according to the level at which they occurred, which means it is not obvious whether these iatrogenic fractures would be evenly distributed across all fractures or would be isolated to a particular group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation